Intraoral Sebaceous Carcinoma: Case Report of a Rare Tumor Emphasizing the Histopathological Differential Diagnosis - Manveen Kaur Jawanda; R. V. Subramanyam; Harshaminder Grewal; Chitra Anandani; Ravi Narula (Case Reports in Dentistry)
Background. Sebaceous carcinoma (SC) is an uncommon cutaneous malignancy, usually occurring predominantly in the eyelids and only occasionally involving the oral cavity. Sebaceous carcinoma (SC) is a rare malignancy. Only 10 cases of sebaceous carcinoma of the oral cavity have been reported so far. Case Presentation. A 40-year-old female presented with a mass on the left side of the middle third of the face. Radiographic findings were inconclusive. Resection of the mass was consistent with the diagnosis of primary sebaceous carcinoma. Conclusion. Intraoral sebaceous carcinoma is uncommon. Due to its varied clinical appearance and presence of a diverse histopathologic appearance, the diagnosis is quite often confounding and elusive. Hence, it is imperative to familiarize oneself about various aspects of this rare tumor for earlier diagnosis, to improve the chances of patient’s survival.